Rapid Institutional Shifts and the Co–evolution of Entrepreneurial Firms in Transition Economies - Ahlstrom, David; Bruton, Garry D. (Entrepreneurship Theory and Practice, 2010)
Economies in transition such as Russia's are among the world's fastest growing. Entrepreneurial firms in an environment like Russia's face rapid and dramatic shifts in the institutional environment. These shifts represent significant challenges to entrepreneurial firms as they seek not only to survive but also to prosper in that environment by rapidly co–evolving with institutional changes. Prior research has focused on institutional change and its impact in developed economies. But the rate of evolution of institutions in transition economies tends to be faster and less predictable. This article reports a longitudinal study of high technology entrepreneurial firms in Russia employing a grounded theory methodology to understand how entrepreneurial ventures co–evolve with rapid institutional changes and still manage to prosper.